2020
DOI: 10.1002/cam4.2838
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐epidermal growth factor receptor monoclonal antibody plus palliative chemotherapy as a first‐line treatment for recurrent or metastatic nasopharyngeal carcinoma

Abstract: Background Platinum‐based chemotherapy is the standard of care as first‐line treatment for recurrent or metastatic nasopharyngeal carcinoma (RM‐NPC); however, the prognosis of patients with RM‐NPC remains poor. The aim of this study was to evaluate the role of anti‐epidermal growth factor receptor (anti‐EGFR) antibody plus chemotherapy for RM‐NPC. Methods RM‐NPC patients who received first‐line chemotherapy plus an anti‐EGFR antibody were recruited from Sun Yat‐Sen University Cancer Center between July 2007 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 31 publications
0
23
1
2
Order By: Relevance
“…EGFR is upregulated in most NPC samples and combination anti-EGFR antibody with chemotherapy is an effective, promising and well-tolerated strategy for recurrent or metastatic NPC 20 , 21 . Extracellular-signal regulated kinase (ERK) is one of downstream molecules of EGFR signaling.…”
Section: Discussionmentioning
confidence: 99%
“…EGFR is upregulated in most NPC samples and combination anti-EGFR antibody with chemotherapy is an effective, promising and well-tolerated strategy for recurrent or metastatic NPC 20 , 21 . Extracellular-signal regulated kinase (ERK) is one of downstream molecules of EGFR signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, radiation therapy is commonly used to treat NPC because the tumor is highly sensitive to ionizing radiation and the anatomical location where it occurs limits the surgical approach. Radiotherapy is generally effective for patients with early and nonmetastatic NPC; therefore, it is the main treatment for the nonmetastatic stages 227,228 …”
Section: Evolution Of Npc Treatmentmentioning
confidence: 99%
“…In a multivariate analysis, the anti‐EGFR agent was an independent prognostic factors for PFS ( P = .010). However, the benefit of anti‐EGFR antibody still warrants further evaluation in larger randomized controlled trails 227 . An ongoing phase III trial is evaluating the efficacy of nimotuzumab versus cisplatin combined with IMRT in patients with stage II‐III NPC (NCT03837808).…”
Section: Evolution Of Npc Treatmentmentioning
confidence: 99%
“…Clinical trials have shown that EGFR-targeted therapy (CTX and NTZ) based on palliative chemotherapy for recurrent or metastatic NPC (R/M NPC) patients significantly increase the chance of progression-free survival (PFS). Moreover, toxic and non-toxic side effects are within a controllable range, suggesting the importance of anti-EGFR therapy in NPC treatment [ 92 ]. CTX and Panitumumab are the most widely used, neutralizing monoclonal antibodies, and inhibit receptor activation and downstream signalling.…”
Section: The Role Of Egfr Targeting In Nasopharyngeal Carcinomamentioning
confidence: 99%
“…Nevertheless, XTC-treated patients have a longer PFS than those who are NTZ-treated, and have an acceptable overall toxicity. Specifically, the toxic effects in patients treated with CTX are more common than in patients treated with NTZ [ 92 ]. The curative effect of the EGFR monoclonal antibody combined with radiotherapy, chemotherapy, and CCRT is equivalent to induction chemotherapy combined with CCRT.…”
Section: The Role Of Egfr Targeting In Nasopharyngeal Carcinomamentioning
confidence: 99%